Sosialisasi Cita-Cita di Era Digital Melalui Pengenalan Profesi Masa Depan Pada Siswa Kelas IV SDN Cibatu 02 - Angghi Apryani; Asma Zakiyah; Deby Anatasya Salsabila (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The way children learn and see the future has been transformed by advances in digital technology. Grade IV students of SDN Cibatu 02 received interactive and contextualized community service. The purpose of this activity was to promote values relevant to the digital age, increase the desire to learn, and instill the value of hard work and innovation. Counseling, discussion, pre- and post-test, and creative activities such as making a poster of ideals were all methods used. The evaluation results show that students have a better understanding of future goals and professions, as shown by the increase in the average post-test score. This activity shows that technology-based and participatory education methods can be a long-term investment to create an adaptive and visionary generation.